2008
DOI: 10.1007/978-1-59745-321-9_27
|View full text |Cite
|
Sign up to set email alerts
|

Gene Essentiality Analysis Based on DEG, a Database of Essential Genes

Abstract: Essential genes are the genes that are indispensable for the survival of an organism. The genome-scale identification of essential genes has been performed in various organisms, and we consequently constructed DEG, a Database that contains currently available essential genes. Here we analyzed functional distributions of essential genes in DEG, and found that some essential-gene functions are even conserved between the prokaryote (bacteria) and the eukaryote (yeast), e.g., genes involved in information storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In COGs, genes can be generally classified into four broad functional categories: information storage & processing, cellular processes & signaling, metabolism and poorly characterized. Previous work has shown that essential genes are overrepresented in the category of information storage and processing with basic cellular functions such as RNA processing and modification and DNA replication [32]. Essential genes involved in this category are often well conserved across species.…”
Section: Resultsmentioning
confidence: 99%
“…In COGs, genes can be generally classified into four broad functional categories: information storage & processing, cellular processes & signaling, metabolism and poorly characterized. Previous work has shown that essential genes are overrepresented in the category of information storage and processing with basic cellular functions such as RNA processing and modification and DNA replication [32]. Essential genes involved in this category are often well conserved across species.…”
Section: Resultsmentioning
confidence: 99%
“…Housekeeping and essential gene networks, as controls for nondisease networks, were built from 2,164 seed genes and their neighbor nodes (2064 for housekeeping and 115 for essential genes) from previous attempts [22,23]. Figure 2B shows the background distribution of similarity values to compute the p values of the disease–disease similarity value, μ.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings on these highly important features for essentiality are concordant with previous studies as follows. First, essential genes tend to be localized in the nucleus, where essential biological processes such as information storage and processing take place (4,16). Second, essential genes are known to be more evolutionarily-conserved than are nonessential genes in bacteria (3) as well as some eukaryotes (17).…”
Section: Resultsmentioning
confidence: 99%